Pengalaman Kehamilan Perempuan Primigravida dengan Riwayat Menikah Usia Dini di Desa Baletbaru Kecamatan Sukowono Kabupaten (The Experience of Primigravida Pregnancy with Child Marriage in Baletbaru Village of Sukowono District) - Rona Gitayanti; Lantin Sulistyorini; Ratna Sari Hardiani (Pustaka Kesehatan, 2016)
A Woman health which need to be understood and undertaken in line with health care services. One of health problems that a Woman often experiences is child marriage. Child marriage is one of the phenomena of Woman health problem in Jember Regency. This research purposes to obtain the experience of primigravida pregnancy with child marriage in the Baletbaru Village. The research used qualitative method, with descriptive phenomenological study design. The sampling technique used purposive sampling with the number of participants as many as 4 people. The study is identifying 8 themes: the desire, assessment of early marriage, a representation of early marriage, normal complaints, pathological complaints, general feeling, special feeling, and the health care what use for. The research results indicated that unreadiness primigravida in physically and psychologically to face child marriage and pregnancy. This research are expected to be the bases for developing policy of marriage and Woman healthcare service. Keywords : Primigravida, Child marriage, Pregnancy experience